EVALUATION OF ANTICONVULSANT ACTIVITY OF PREMNA HERBACEA (ROXB.) EXTRACTS IN PENTYLENETETRAZOL AND MAXIMAL ELECTROSHOCK-INDUCED CONVULSIONS IN MICE - Chimbalkar, Ashish Dattatraya; Ns, Vyawahare (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present study, three different extracts of Pemna herbacea (Roxb.) were evaluated for its anticonvulsant activity against pentylenetetrazol (PTZ) and maximal electroshock (MES)-induced convulsions in mice. Methods: The shed-dried powder of P. herbacea roots was passed through a sieve and subjected to extraction using Soxhlet apparatus with 70% ethanol, petroleum ether, and chloroform to get respective extracts named as ethanolic extract of P. herbacea, petroleum ether extract of P. herbacea, and chloroform extract of P. herbacea (PHC). Preliminary phytochemical analysis and acute oral toxicity study were done. Thereafter, the extracts were analyzed for PTZ- and MES-induced convulsions. Results: The results revealed that PHC at the doses 200 and 400 mg/kg was effective against both, i.e., PTZ- and MES-induced convulsions. Overall PHC 400 mg/kg was most effective, as it significantly delayed onset of convulsions (p<0.01) and reduced % mortality (50%) in PTZ model, while in MES model, it showed the highest reduction in duration of hind limb extension (p<0.01) and percentage protection (33.33%). Conclusion: The results reported anticonvulsant potential of PHC against both PTZ- and MES-induced convulsions suggesting mixed mechanism of action which may be attributed to different phytochemicals acting simultaneously. Â 